Resilience in Promotion of Schools as Learning Organisations: Reflections on Karnataka Experience - Diwan, Rashmi (JOURNAL OF INDIAN EDUCATION, 2009)
Present scenarios of school education in India portrays school as a rigid system of teaching-learning where teaching processes dominate over learning. Children voices do not have any place in the classroom. Teachers do not reflect themselves as lifelong learner. Deliberating on this crucial aspect of Indian Education system this article makes a plea before all the stakeholders to transform the schools from teaching organisation to learning organisation. The paper strongly recommends that in today’s world, each school must become a learning organisation.The paper strongly recommends that in today’s world, each school must become a learning organisation. Looking at the possibility of transforming schools into learning organisations, the two practices namely, the H.D Kote and Kalikayatna in Karnataka reflects on the success with which schools have been providing rich learning experiences in all its activities right from curriculum transaction to teacher training. Highlighting the quintessential characteristic of schools as organisations that learn, the paper suggests some workable propositions by which schools inspite of functioning in bureaucratic framework can become learning organisations.